From laboratory to clinical practice: an update of the immunological and molecular tools for neurocysticercosis diagnosis - Toribio, Luz M.; Bustos, Javier A.; Garcia, Hector H. (Frontiers in Parasitology, 2024)
Neurocysticercosis (NCC) is caused by the invasion of Taenia solium larvae to the central nervous system (CNS) and stands as the predominant cause of epilepsy and other neurological disorders in many developing nations. NCC diagnosis is challenging because it relies on brain imaging exams (CT or MRI), which are poorly available in endemic rural or resource-limited areas. Moreover, some NCC cases cannot be easily detected by imaging leading to inconclusive results. Multiple laboratory assays, principally immunological, have been developed to support diagnosis and/or monitor the treatment efficacy; but its production can be costly, laborious and non-globally accessible because they depend on parasite material. Therefore, recent advances have been focused on the implementation of recombinant or synthetic antigens, as well as monoclonal antibodies for NCC immunodiagnosis purposes. Similarly, molecular diagnosis has been explored obtaining promising results. Here, we described the recent progress in the development immunological and molecular diagnostic tools for NCC diagnosis over the past 13 years, discussing their potential application to address important challenges and how to focus future directions to improve NCC diagnosis with emphasis in enhance accessibility and the importance of test validation to provide an adequate support for clinical decisions.